Strengthening Religious Character Education of Students Based on School Culture - Lestari, Dwi Putri Ayu; Amrullah, Muhlasin; Hikmah, Khizanatul (research, training and philanthropy institution Natural Aceh, 2023)
This study aims to describe strengthening the religious character education of grade IV students at SD Muhammadiyah 11 Randegan. This study uses a qualitative research approach with a phenomenological research type with data collection techniques using interviews, observation and documentation. Data analysis techniques using the interactive model of Miles, Huberman and Saladana include data collection, data condensation, data presentation, and conclusion drawing. The data validity test technique uses triangulation, namely source triangulation and technique triangulation. The results showed that strengthening religious character education can be through a school culture consisting of tahfidz Al-Qur'an, ta'lim muta'alim activities, congregational prayers, habituation of greetings, muhasabah activities, Friday blessing activities and commemoration of religious holidays. The impact of school culture activities to strengthen the religious character education of fourth-grade students at SD Muhammadiyah 11 Randegan has a positive impact where this activity has been implemented quite well, which is evidenced by improving the attitude of students who change significantly, such as increasing the awareness of students in performing prayers, increasing the attitude of concern for others who are in need, developing an attitude of tolerance, and better understanding the manners in Islam that have been taught by teachers at school and applied in everyday life.